2007
DOI: 10.1089/ars.2007.1745
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Targeting the Nrf2 Pathway by Triterpenoids (CDDO-Im and CDDO-Me) for Protection from LPS-Induced Inflammatory Response and Reactive Oxygen Species in Human Peripheral Blood Mononuclear Cells and Neutrophils

Abstract: Sepsis is characterized by an inappropriate host immune-inflammatory response and sustained oxidative damage. Nrf2, a bZIP oxidant-responsive transcription factor, regulates a battery of cytoprotective genes including antioxidants and maintains cellular redox homeostasis. Mouse studies have demonstrated a critical role of Nrf2 in improving survival during sepsis. This preclinical ex vivo study using neutrophils and peripheral blood mononuclear cells (PBMCs) as a surrogate cells evaluates the efficacy of CDDO-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
116
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 40 publications
(56 reference statements)
9
116
3
Order By: Relevance
“…Interestingly, it was reported that this regulation of TNF-induced VCAM-1 expression was not through NF-kB inhibition. Thimmulappa et al (9) reported that CDDO-Im (a synthetic triterpenoid) induces a number genes, including NQO1 in neutrophils, and was associated (coincided) with the inhibition of LPS-induced IL-6 and TNF induction. The results of the current study show that TNF-induced expression of NQO1 in combination with other Nrf2-regulated genes can inhibit TNF-induced TNF and IL-1b expression in human monocytes, and that this inhibition seems to be sustained and NF-kB dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it was reported that this regulation of TNF-induced VCAM-1 expression was not through NF-kB inhibition. Thimmulappa et al (9) reported that CDDO-Im (a synthetic triterpenoid) induces a number genes, including NQO1 in neutrophils, and was associated (coincided) with the inhibition of LPS-induced IL-6 and TNF induction. The results of the current study show that TNF-induced expression of NQO1 in combination with other Nrf2-regulated genes can inhibit TNF-induced TNF and IL-1b expression in human monocytes, and that this inhibition seems to be sustained and NF-kB dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the transcription factor NF-E2-related factor 2 (Nrf2) has emerged as a key regulator of inflammation (8,9). The main role of Nrf2 is to protect cells from oxidative damage by inducing the expression of various cytoprotective and detoxification genes (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was based on the findings that, in addition to directly binding to IKKβ, CDDO has been described to induce expression of enzymes catalyzing antioxidant reactions in peripheral blood mononuclear cells due to increased nuclear accumulation of Nrf2, an oxidant-responsive bZIP transcription factor. 40,41 Whereas EP is an effective ROS scavenger in irradiated zebrafish embryos, CDDO-TFEA did not reduce ROS levels measured 2 hours after radiation exposure ( Supplementary Fig. S5).…”
Section: The Ikk Inhibitor Cddo-tfea Mitigates Radiation Effects In Zmentioning
confidence: 95%
“…ROS and peroxynitrite inhibit CD8 + T cells by catalyzing the nitration of the TCR and preventing T cell-peptide-MHC interactions essential for CD8 + activation (Wiers et al, 2000). MDSCs have thus emerged as a potential target in cancer immunotherapeutics with triterpenoids (Thimmulappa et al, 2007), arginase (Serafini et al, 2008), cyclooxygenase 2 (Sinha et al, 2007), phosphodiesterase-5 inhibitors (Serafini et al, 2006), and nitroaspirin (Nagaraj et al, 2010;Molon et al, 2011;Mundy-Bosse et al, 2011) (Mills et al, 2000). The poor antigen-presenting capability of TAMs accounts for their immune-suppressive functions.…”
Section: Role Of Myeloid-derived Suppressor Cells In Tumor Immunosuppmentioning
confidence: 99%